PENYULUHAN KESETARAAN GENDER DAN SUPORT KEMANDIRIAN PEREMPUAN DALAM AL-QURAN DI YAYASAN BALQIS - Nur Arfiyah Febriani; Isyfi Anny Azmi Al Rozi; Baeti Rahman; Andi Rahman; Muhammad Hidayat; Imam Addaruqutni (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The issue of gender inequality has become the focus of deep debate in the context of understanding the Koran. This article examines a balanced approach to interpreting the Qur'an in understanding verses relating to women, with the aim of supporting women's empowerment in Islamic society. Qualitative methods and descriptive approaches are used in this paper. The emphasis on historical and social context in the interpretation of the Qur'an is strengthened to understand verses that are relevant to the reality of women today. Thus, this article voices the need for a holistic and in-depth interpretive approach so that the Al-Qur'an can become a source of inspiration for empowering women and overcoming gender inequality in Muslim society. As a result, it was found that what is conveyed in the Koran actually refutes societal stereotypes that consider Islam to be unfair to women. In its early days, the Arab practice of polygamy allowed men to have multiple wives without restrictions. However, Islam regulates this by limiting it to four or even just one wife. In addition, the Koran and Islam no longer exclude women from their presence in public spaces, by giving them the right to provide testimony. The Qur'an and Islam also pay attention to women's safety by instructing them to dress modestly to protect themselves from harassment. Nowadays, efforts to fight for gender equality in the Islamic world are starting to show promising developments. Most Muslim countries are currently making progress in fulfilling women's rights, although they have still not fully resolved problems relating to women in the Islamic context. In Indonesia, the issue of gender equality is increasingly gaining support with the emergence of several thinkers and institutions that care about gender issues